Hematological ratios, immune-related adverse events and mortality in patients treated with immune checkpoint inhibitors - Sophie Lekkerkerker; Karin A. H. Kaasjager; Saskia Haitjema; Cornelia Hulsbergen-Veelken; Karin H. Herbschleb; Marianne C. Verhaar; Meriem Khairoun; Gurbey Ocak (PLoS ONE, 2025)
Background Although immune checkpoint inhibitors improve survival in patients with malignancies, a substantial number of patients treated with these agents experience immune-related adverse events. It is unknown whether inflammation-related hematological ratios are associated with immune-related adverse events or mortality. Objective We aimed to investigate the association between pretreatment inflammation-related hematological ratios and the occurrence of immune-related adverse events and mortality in patients receiving checkpoint inhibitors. Methods Patients treated with checkpoint inhibitors within a tertiary hospital in the Netherlands were studied using routine care data between January 2013 and May 2020. Cox regression analysis was performed to assess the association between neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocytes and platelets ratio (NLPR), and systemic immune-inflammation index (SII) and outcomes (immune-related adverse events or mortality). Results Among 664 patients treated with checkpoint inhibitors, 397 (59.8%) patients developed an immune-related adverse event and 363 (54.7%) patients died during a median follow-up period of 17 months (interquartile range 7–30 months). Hematological ratios were not associated with immune-related adverse events. However, highest tertiles as compared with lowest tertiles of all hematological ratios were independently associated with mortality (NLR: adjusted hazard ratio (HR) 2.23, 95% CI 1.69–2.95; PLR: adjusted HR 1.88, 95% CI 1.43–2.47; NLPR: adjusted 1.59, 95% CI 1.22–2.06; SII: adjusted HR 2.33, 95% CI 1.77–3.08). Conclusion In this study, pretreatment inflammation-based hematological ratios were not associated with future immune-related adverse events in patients treated with checkpoint inhibitors. However, elevated hematological ratios were associated with an increased mortality risk.